Answer to Question #215948 in Differential Equations for Bashar

Question #215948

( 1 /t + 1/ t ^2 − y /t ^2 + y ^2 ) d t + ( y e ^y + t /t ^2 + y^ 2 ) d y = 0


1
Expert's answer
2021-07-18T08:58:39-0400

"( {1 \\over t} + {1\\over t ^2} \u2212 {y \\over t ^2 + y ^2 }) d t + ( y e ^y +{ t \\over t ^2 + y^ 2 }) d y = 0"


"M(t,y)=" "( {1 \\over t} + {1\\over t ^2} \u2212 {y \\over t ^2 + y ^2 })"


"\\implies { \\partial M(t,y)\\over \\partial y}=M_y=-{1(t^2+y^2)-2y(y) \\over (t^2+y^2)^2}=-{t^2+y^2-2y^2\\over (t^2+y^2)^2}=-{t^2-y^2\\over (t^2+y^2)^2}={y^2-t^2\\over (t^2+y^2)^2}"


"N(t,y)=( y e ^y +{ t \\over t ^2 + y^ 2 })"


"\\implies { \\partial N(t,y)\\over \\partial t}=N_t={y^2-t^2\\over (t^2+y^2)^2}"


The differential equation is exact since "M_y=N_t"


There exist a function "\\mu(t,y)" such that


"{\\partial \\mu (t,y)\\over \\partial t}=M(t,y)=( {1 \\over t} + {1\\over t ^2} \u2212 {y \\over t ^2 + y ^2 })"


"{\\partial \\mu (t,y)\\over \\partial y}=N(t,y)=( y e ^y +{ t \\over t ^2 + y^ 2 })"


Let "\\mu (t,y)=\\int^yN(t,y)dy" "+" "g(t)"


"=\\int^y( y e ^y +{ t \\over t ^2 + y^ 2 }) dy" "+" "g(t)"


"=ye^y-e^y+tan^{-1}({y\\over t})+g(t)"


"\\implies {\\partial \\mu (t,y)\\over \\partial t}=-{y\\over t^2+y^2}+{\\partial g(t)\\over \\partial t}={1 \\over t} + {1\\over t ^2} \u2212 {y \\over t ^2 + y ^2 }"


"\\implies {\\partial g(t)\\over \\partial t}={1 \\over t} + {1\\over t ^2}"


"\\implies \\int dg(t)=\\int( {1 \\over t} + {1\\over t ^2})dt"


"\\implies g(t)=ln(t)-{1\\over t}"


"\\implies \\mu(t,y)=ye^y-e^y+tan^{-1}({y\\over t})+ln(t)-{1\\over t}"


"\\therefore" The general solution is thus


"ye^y-e^y+tan^{-1}({y\\over t})+ln(t)-{1\\over t}=c"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog